2020
DOI: 10.1177/0268355520938578
|View full text |Cite
|
Sign up to set email alerts
|

Bioimpedance spectroscopy and volumetry in the immediate/short-term monitoring of intensive complex decongestive treatment of lymphedema

Abstract: Aims To assess (a) immediate/short-term outcomes of intensive complex decongestive treatment of lower limb lymphedema, by means of bioimpedance spectroscopy and tape measurement-based volumetry, and (b) correlation between these two methods. Patients and methods Cohort study on patients affected by unilateral primary or secondary lymphedema, stage II or III. Patients underwent complex decongestive treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…In another study, performed by Kostanoğlu and colleagues (2019), a reduction between 296 mL and 1038 mL, depending on the stage of lymphedema, was reported after 4 weeks of complete decongestive therapy [ 7 ]. A recent study by Cavezzi and colleagues (2020) also showed a short-term reduction of limb volume using perometry after 6 days of complete decongestive therapy [ 28 ]. We observed similar effects in our study after 21 days.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, performed by Kostanoğlu and colleagues (2019), a reduction between 296 mL and 1038 mL, depending on the stage of lymphedema, was reported after 4 weeks of complete decongestive therapy [ 7 ]. A recent study by Cavezzi and colleagues (2020) also showed a short-term reduction of limb volume using perometry after 6 days of complete decongestive therapy [ 28 ]. We observed similar effects in our study after 21 days.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, data on the use of bioimpedance analysis in disease tracking after lymphedema treatment remains insufficient. Both Cho et al and Cavezzi et al considered that bioimpedance analysis is feasible for detecting slight extracellular fluid changes after complex decongestive therapy [36,37], and therefore, is practical for outcome monitoring. For surgical intervention of lymphedema, Sutherland et al first utilized BIS to assess the effect of lymphovenous bypass for breast cancer-related lymphedema, and reported clinically significant improvement after lymphovenous bypass [38].…”
Section: Discussionmentioning
confidence: 99%
“…Before starting the data collection, all the patients were trained to carry out the BIA measurements by themselves by means of a portable multifrequency instrument (Biody Xpert IITM; eBIODY SAS La Ciotat, France). The multiple frequencies delivered by the instrument ranged from 5 kHz to 200 kHz, while R, Xc, and PA were settled at 50 kHZ [11][12][13][14][15]. Soon after the recording, all the data were transferred via Bluetooth technology on a computer and stored under a personal patient folder.…”
Section: Bioimpedance Analysis (Bia)mentioning
confidence: 99%
“…The body fluid composition assessment made by BIA is based on the inverse correlation between body resistance and the TBW, by means of the calculation on different prediction equations [9,10]. Moreover, other important physical parameters of BIA are resistance (R), indicating the fluid contents, and reactance (Xc), representing tissue composition [11][12][13]. Phase angle (PA) is another relevant BIA parameter, obtained by the relationship between R and Xc, and thus associated with cellularity, cell size, and integrity of the cell membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation